COMPLICATION RATES OF IVIG IN INFLAMMATORY NEUROPATHY. Issue 12 (15th November 2016) - Elhadd, Kariem; Khan, Sidra; Gosal, David; Woodall, Amanda; Nasr, Eman; Sharaf, Nazar
Abstract : Background: This study reports the complication rate of intravenous immunoglobulin in patients with inflammatory neuropathy in a tertiary neurology centre over 5 years. Methods: A retrospective analysis was conducted using audited hospital records of reported adverse reactions and corroboration with data from DoH database in patients undergoing IVIG therapy for inflammatory neuropathy between the years 2010 and 2014. The study sample consisted of 36 patients who suffered 42 complications during 5909 infusions within this time period. The complication rate was calculated using the mean of the 5 years expressed as complications per 100 infusions per year. The types of complications were classified and described based on frequency per year and overall over 5 years. Results: The analysis revealed a mean complication rate of 0.71 per 100 infusions per year between 2010 and 2014 in a tertiary Neuroscience Centre. Dermatological complications were most frequent. Conclusion: We found in the average complication rate if IVIG over 5 years is 0.71 per 100 infusions per year in patients with inflammatory neuropathy in a Tertiary Neurology Centre. Dermatological complications were the most frequent adverse reaction. We recommend new efforts to identify at risk patients of complications.